HUBUNGAN PENGETAHUAN DAN SIKAP IBU RUMAH TANGGA DENGAN PENGGUNAAN GARAM BERYODIUM - Yunita Syahputri Damanik (Jurnal Penelitian Kesmasy, 2019)
A long-term sustainable effort is by iodizing salt, which is adding iodine to food ingredients. The aim of this program is that 90% or more households consume iodized salt according to the requirements, which is 30-80 parts permillion (ppm). The aim of this research was to determine the relationship between knowledge and attitudes of the housewives with the use of iodized salt in Delitua Timur, Deli Serdang. The sampling technique in this research was non probability sampling using a purposive method of 96 people. The analysis carried out using the chi-square test. The results of the research on 96 respondents for the knowledge variable obtained which means there was not relationship between knowledge and the use of iodized salt. And for attitude variables obtained which means there was a relationship between attitudes and use of iodized salt in Delitua Timur, Deli Serdang. The suggested for this research to the society to increase their knowledge and positive attitude to use of iodized salt in an effort to improve health and nutrition.